Serum IL-10 as a marker of severe dengue infection. - Malavige, G; Gomes, L; Alles, L; Chang, T; Salimi, M; Fernando, S; Nanayakkara, K; Jayaratne, S; Ogg, G (BioMed Central, 2013)
BACKGROUND: Several studies have shown that serum IL-10, IFNγ and MIF are elevated in patients in severe dengue (SD) and could be used as potential biomarkers. We proceeded to determine if these cytokines could be used as biomarkers in a large cohort of adult dengue patients with varying severity of dengue infection. METHODS: Serum IL-10 levels were determined in 259 of whom 40 had severe dengue infection. Serum IFNγ and IFNα levels were done in 78 and MIF levels were done in 65 patients with acute dengue infection. Clinical features and laboratory investigations were undertaken during the febrile and critical phase. RESULTS: We found that serum IL-10 levels were significantly higher (p = 0.001) in patients with SD, when compared to those with non SD. Serum IL-10 levels significantly and inversely correlated with white cell counts (R = -0.23, p = 0.0002) and lymphocyte counts (R = -0.29, p < 0.0001) but significantly and positively correlated with aspartate tranaminase levels (R = 0.16, p = 0.01) and alanine transaminase levels (R = 0.22, p = 0.007). However, IL-10 levels did not have a good predictive value in discriminating those who were likely to develop SD (AUC = 0.66). Serum IFNγ levels were also significantly higher (p = 0.04) in patients with SD when compared to non SD. There was no difference (p = 0.34) in serum IFNα levels and serum MIF levels (p = 0.15) in patients with SD and non SD. CONCLUSION: Although serum IL-10 was significantly elevated in patients with SD it had a poor discriminatory value in identifying those with SD and non SD and therefore, is unsuitable to be used as a robust biomarker in this cohort.